2019
DOI: 10.1016/j.jjcc.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of low admission hemoglobin over the GRACE score in patients with acute coronary syndrome

Abstract: A B S T R A C TBackground: The GRACE risk score is currently recommended as the major score for risk prediction on admission in patients with acute coronary syndrome (ACS). Anemia in patients with ACS adversely affects their clinical outcomes, yet hemoglobin level on admission is not included as a parameter in the GRACE score. We hypothesized that hemoglobin level on admission would improve the predictive value of the GRACE score. Methods: We retrospectively studied one-year mortality in consecutive ACS patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
0
9
1
Order By: Relevance
“…15 Furthermore, anemia (Hb <12 g/ dl) on admission is associated with increased mortality in ACS patients. 16,17 However, the mean Hb concentration found in this study is in the normal range.…”
Section: Discussioncontrasting
confidence: 63%
“…15 Furthermore, anemia (Hb <12 g/ dl) on admission is associated with increased mortality in ACS patients. 16,17 However, the mean Hb concentration found in this study is in the normal range.…”
Section: Discussioncontrasting
confidence: 63%
“…21 Moady et al's study suggested that in patients with a low GRACE score (<140), anemia on admission has additional predictive value for 1-year mortality. 22 Chattopadhyay et al also established an adjusted GRACE score by adding 2-hour postload glucose, which can improve prediction of long-term major adverse cardiac events in ACS patients without known diabetes. 23 Cordero et al integrated the CRUSADE and GRACE scores to estimate mortality risk and found the predictive power to be significantly improved.…”
Section: Thrombosis and Haemostasismentioning
confidence: 99%
“…A number of previous studies show that the GRS has a predictable probability for MACE composited of death and MI. [ 5 , 10 , 14 , 41 ] Although the study by Fan et al of Chinese STEMI patients finds some association between the GRS and complex cardiovascular events, [ 42 ] our study finds the predictive ability of the GRS on multiple major adverse events to remain inadequate and further work is required. Nevertheless, the disparity between our and Fan et al results could be due to the lower rate of cardiovascular death and MACE in our center, which is owed by the timely reperfusion and complete revascularization in accordance with current guidelines and management of STEMI.…”
Section: Discussionmentioning
confidence: 74%